Effect of maternal smoking during pregnancy on Tourette syndrome and chronic tic disorders among offspring: a systematic review and meta-analysis - Erfan Ayubi; Kamyar Mansori; Amin Doosti-Irani (Obstetrics & Gynecology Science, 2021)
Current studies have controversial reports about the effect of maternal smoking during pregnancy (MSDP) on the risk of psychiatric disorders among offspring. The purpose of this systematic review and meta-analysis was to assess the effect of MSDP on the risk of Tourette syndrome (TS) and chronic tic disorders (CTD) among offspring. A systematic search using PubMed, Scopus, and Web of Science was conducted up to July 2019 to retrieve potential studies in English. Fixed and random-effects meta-analyses was performed to estimate pooled relative risk (RR) with 95% confidence interval (CI) according to heterogeneity. The methodological quality of the included studies was evaluated using the Newcastle-Ottawa Scale. Heterogeneity among studies was explored using the I2 statistic. Of the 641 studies from the initial search, 7 were included in the quantitative synthesis (3 cohort and 4 case control studies). Overall, MSDP increased the risk of TS and CTD among the offspring by 35% (pooled RR, 1.35; 95% CI, 1.17–1.56; I2=45.8%; P-value=0.08). The results of this meta-analysis revealed that there is a significant association between MSDP and the risk of TS and CTD in offspring, and MSDP may be considered a potential risk factor for TS and CTD.